Meta-Analysis of the Role of Women in the Development of MSMES - Indriani, Annisa; Sinaga , Dara Balqis Fariha; Ingtyas , Fatma Tresno; Ginting , Laurena (Journal Corner of Education, Linguistics, and Literature, 2024)
The role of women in the development of Micro, Small, and Medium Enterprises (MSMEs) has a significant impact, especially in developing countries. Women have made substantial contributions in managing businesses, ranging from micro to medium scale. This study aims to examine the role of women in the development of MSMEs through a meta-analysis of various previous studies. The analysis shows that women play an important role in capital management, production, distribution, and marketing of MSMEs, despite facing challenges such as dual roles, lack of family support, limited access to finance, and insufficient training and personal development opportunities. Nevertheless, women demonstrate remarkable resilience by utilizing digital marketing and supporting government policies such as the KUR (People's Business Credit) and UMi (Ultra Micro) programs. Education, experience, and a positive attitude toward risk also play a vital role in the success of female entrepreneurs. To enhance women's contributions to MSMEs, it is essential to improve access to entrepreneurial training, better business management practices, and support from families and communities. With the right steps, women's empowerment can strengthen the local economy, create jobs, and reduce gender gaps, making MSMEs more inclusive and sustainable.